Intradural squamous cell carcinoma in the sacrum - Fujisawa Kozo; Kato Ko; Kasai Yuichi; Fukushima Tatsuki; Uchida Atsumasa (World Journal of Surgical Oncology, 2009)
Abstract Background Leptomeningeal carcinomatosis occurs in patients with cancer at the rate of approximately 5%; it develops particularly in patients with breast cancer, lung cancer, melanoma, leukemia, or malignant lymphoma. We describe a rare case of leptomeningeal carcinomatosis in which spinal intradural squamous cell carcinoma with no lesions in the cerebral meninges and leptomeninx, was the primary lesion. Methods A 64-year-old man complained of sacral pain. Although the patient was treated with analgesics, epidural block and nerve root block, sacral pain persisted. Since acute urinary retention occurred, he was operated on. The patient was diagnosed as having an intradural squamous cell carcinoma of unknown origin. Results Since the patient presented with a slightly decreased level of consciousness 2 months after surgery, he was subjected to MRI scanning of the brain and spinal cord, which revealed disseminated lesions in the medulla oblongata. The patient died of pneumonia and sepsis caused by methicillin-resistant Staphylococcus aureus 5 months after surgery. Conclusion We report the first case of a patient with intradural squamous cell carcinoma with unknown origin that developed independently in the sacrum.